The effects of cognitive and motivational imagery on acquisition, retention and transfer of the basketball free throw - VaezMousavi, S. M.; Rostami, R. (World Journal of Sport Sciences, 2009)
The present study was designed to compare the effects of physical practice, cognitive imagery accompanied with physical practice and motivational imagery accompanied with physical practice on acquisition, retention and transfer of the Basketball free throw. Seventy-eight female students with no prior experience in the task participated in the study in partial fulfillment of the requirements for their P.E. course. They were assigned in three groups according to the results of Motor Imagery Ability questionnaire, Sport Imagery Questionnaire and pretest scores. All groups participated in eighteen sessions of practices and acquisition, retention and transfer tests. The results of one way ANOVA indicated that physical practice group was better in acquisition phase, but cognitive imagery group produced better results in retention and transfer tests. These results pointed out that the cognitive functions of the mental imagery, not the motivational functions, may improve the processes of learning a new motor skill.